The wisdom of the enneagram : the complete guide to psychological and spiritual growth for the nine personality types - Riso, Don Richard (Bantam Books, 1999)
Provides insight for determining personality types, from recognizing each type's wake-up call and red flag to letting go of self-defeating habits and reactions.